Development of MQL (minimum quantity lubricant) automation in applying cutting fluid on lathes - Aris Zainul Muttaqin; Mahros Darsin; Yohan Rizal Kharisma; Ahmad Syuhri; Muhammad Trfiananto (Politeknik Negeri Lhokseumawe, 2022)
It is normal to apply cutting fluid to machining, but using it excessively will harm the environment. One of the efforts to reduce it is to apply minimum quantity lubrication (MQL). This study aims to minimize the use of cutting fluid by designing a cutting fluid delivery system with Arduino Uno control. The developed MQL system can be controlled both based on temperature and time. This MQL system was a development from the previous system by replacing the limit and temperature sensor, nozzle, and mini compressor with a sprayer. The performance of this new MQL system was compared to a flooded cutting fluid feeding system. The experimental design of Taguchi L9 (3^4) with additional varied factors such as depth of cut, cutting speed, and feed rate. Each factor consisted of 3 levels. The measured output was cutting fluid consumption. S/N ratio analysis showed that the method of giving the cutting fluid most dominantly affected the outcome. ANOVA showed that more than 97.56% of the factors were dominated by the method. The combination of factors that would produce a minimum burst at a rate of 180 ml/hour if applying a combination of factors and a level of depth of cut 1.8 mm and a cutting speed of 120.89 m/min, provision of cutting fluid with the periodic MQL method and feed rate of 0.122 mm/rev. Meanwhile, the metal removal rate (MRR) analysis recommended the use of periodic cutting fluid methods at a depth of cut of 2.2 mm. The development of the new MQL either temperature control or periodic system control, both were able to comply with the MQL criterion, i.e. the maximum spray of 500 ml/h.